PERAN GURU SEBAGAI FASILITATOR DALAM TRANSFORMASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Siti Su'adah; Ahmad Hariandi; Andi Gusmaulia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of teachers as facilitators in the transformation of the independent curriculum in elementary schools. The research method used in this study is a qualitative method. The subjects of this study were class IVA teachers at SD Negeri 34/I Teratai. Data collection techniques were carried out through observation, interviews and document studies. The results of the study indicate that class IVA teachers have carried out their roles as facilitators in the transformation of the independent curriculum in elementary schools well through the observed indicators, namely learning planning through the provision of learning tools, organizing learning by providing learning facilities, implementing learning by acting as partners, not superiors, assessing the learning process through the application of the principle of justice.